Anticipation as Platform Power: The Temporal Structuring of Digital Everyday Life - Koivunen Anu; Nikunen Kaarina; Hokkanen Julius; Jaaksi Vilja; Lehtinen Vilma; Soronen Anne; Talvitie-Lamberg Karoliina; Valtonen Sanna (Sage, 2025)
This article explores anticipation as a temporal structure in digital platforms. It contributes to the growing research of platformisation of everyday life by focusing on temporality as a central dimension of platform power, a key mechanism tying participants by structuring intimacies, socialities, and relations that platforms enable and engender. The article shows how the temporality of foreboding, prospecting and speculating about one’s own and other’s social media presence and actions permeates the user experience. Studying media diaries and interviews with participants from different social and occupational groups (politicians, actors, the unemployed, undocumented migrants), the article analyses anticipation as a structure of feeling, as time- and energy-consuming digital labor and as the embodiment of platform power’s mechanisms. While anticipation has previously been examined as operational logics of the platform economy, this article demonstrates how anticipation also concerns ordinary media users on the level of their everyday life worlds, experiences and practices.